2006
DOI: 10.1007/s10562-006-0168-x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Cu–Mn oxides mediate efficiently TEMPO-catalyzed aerobic oxidation of alcohols

Abstract: Cu-Mn oxides in combination of 2,2,6,6-tetramethyl-piperidyl-1-oxy (TEMPO) were firstly used to catalyze aerobic selective oxidation of alcohols to carbonyl compounds. Such recyclable heterogeneous cocatalysts showed good catalytic performance in the process when the molar ratio of Cu and Mn is over 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Other manganese‐based systems were applied for alcohol oxidation, namely, silica‐supported manganese dioxide (MnO 2 ) in the oxidation of benzyl alcohol under solvent‐free conditions,72 which yielded 88 % of acetophenone under MW for 20 s. However, this system required excess MnO 2 relative to the substrate (5:1 molar ratio), whereas in the present study we have achieved 72 % yield by using a maximum of 1 % molar ratio of catalyst relatively to substrate. Furthermore, mixed Mn–Cu or Mn–Co nitrates70 and heterogeneous Cu–Mn mixed oxides71 in combination with TEMPO have been employed for the selective aerobic oxidation of a variety of alcohols to the corresponding aldehydes and ketones under mild conditions. In our case, a significant yield increase was observed for the 1‐phenylethanol oxidation in the presence of 1 (from 36 % in the absence of TEMPO to 57 % in its presence; Table 2, Entries 5 and 14).…”
Section: Resultsmentioning
confidence: 99%
“…Other manganese‐based systems were applied for alcohol oxidation, namely, silica‐supported manganese dioxide (MnO 2 ) in the oxidation of benzyl alcohol under solvent‐free conditions,72 which yielded 88 % of acetophenone under MW for 20 s. However, this system required excess MnO 2 relative to the substrate (5:1 molar ratio), whereas in the present study we have achieved 72 % yield by using a maximum of 1 % molar ratio of catalyst relatively to substrate. Furthermore, mixed Mn–Cu or Mn–Co nitrates70 and heterogeneous Cu–Mn mixed oxides71 in combination with TEMPO have been employed for the selective aerobic oxidation of a variety of alcohols to the corresponding aldehydes and ketones under mild conditions. In our case, a significant yield increase was observed for the 1‐phenylethanol oxidation in the presence of 1 (from 36 % in the absence of TEMPO to 57 % in its presence; Table 2, Entries 5 and 14).…”
Section: Resultsmentioning
confidence: 99%
“…The reported catalytic systems are exemplified by both homogeneous (Semmelhack et al 1984; Greene et al 2015) and heterogeneous procedures (Bolm and Fey 1999; Yang et al 2006). It is well-known that both of these procedures have their advantages and drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of investigations have revealed that 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) and its derivatives are some of the most efficient catalysts for the selective aerobic oxidation of alcohols to the corresponding carbonyl compounds (de Nooy et al 1996 ). The reported catalytic systems are exemplified by both homogeneous (Semmelhack et al 1984 ; Greene et al 2015 ) and heterogeneous procedures (Bolm and Fey 1999 ; Yang et al 2006 ). It is well-known that both of these procedures have their advantages and drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…Benzaldehyde was the sole reaction product with 97% conversion of benzyl alcohol in 4 hours under reflux conditions, using excess of air or oxygen as stoichiometric oxidant. Similarly Yang et al [18] have studied the oxidation of benzyl alcohol to benzaldehyde catalysed by C -Mn oxide catalyst supported on carbon at 353 K. Yang et al [19] studied the oxidation of benzyl alcohol with 100% selectivity to benzaldehyde using MnO 2 as catalyst in the presence of 2,2,6,6-tetramethyl-piperidyl-1-oxy (TEMPO). About 23% and 36% benzyl alcohol was converted to benzaldehyde in 6 hours at 393 K with and without TEMPO.…”
Section: Introductionmentioning
confidence: 99%